Marvel-verse. Iron Man. - Van Lente, Fred; Michelinie, David; Busiek, Kurt (Marvel Worldwide, Inc, 2019)
A collection of four graphic novel stories featuring Iron Man's origins, his collaboration with Spider-Man against Radioactive Man, his return to his public business life, and his encounter with Doctor Doom.